Internatonal Trade and Aid Allocation Decisions on a Network Basis - Li, Che. (2017)
Abstract: In order to study the self-interest motivation when allocating aid to developing countries, I build a theoretic model based on network theory and input-output economy using a baseline Ricardian international trade setup. The model suggests that disaggregate fluctuations in developing country potentially propagate via international trade and interconnectivity of upstream and downstream industries and cause amplified impact on aggregate productivity in the developed country. I examine the effect of intermediate goods share on aid allocation decision of a donor country facing disasters in the recipient country using a cross-sectional model and a panel model. I found evidence supporting the results of the theoretic model and intermediate goods share of import between donor and recipient countries has a significantly positive impact on aid allocation decision and has a less persistent effect when disasters occur during the past in the recipient country. My study raises the question: How is this mechanism going to affect the effectiveness of aid on growth? Is there case-study that supports the general idea of this model and provides insight on how self-interested aid allocation motives hinders growth?; Thesis (M.S.)--Tufts University, 2017.; Submitted to the Dept. of Economics.; Advisor: Sahar Parsa.; Committee: Alan Finkelstein-Shapiro.; Keyword: Economics.